2019
DOI: 10.13040/ijpsr.0975-8232.10(6).2970-74
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Quality of life is an essential measure that proves the effectiveness of health care, health level, and well-being. Kidney diseases are one of the major health problems that affect Quality of life. This study aimed to assess the quality of life in dialysis (CRF-D) and non-dialysis (CRF-ND) chronic renal failure (CRF) patients using Kidney Disease Quality of Life-short form (KDQOL-SF TM ) and identify the differences in disease symptoms between these two groups. 200 CRF patients were included in the study. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Interestingly, we showed that the administration of RONS to patients with nondialysis CKD rendered their QoL stationary. Frequently, QoL decreases as the severity of CKD rises [35,36], albeit study results can be heterogenous [37]. These discrepancies in reported findings may stem from the tools used, the etiology of CKD, the degree of patient's adherence to their prescriptions of RONS, etc.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, we showed that the administration of RONS to patients with nondialysis CKD rendered their QoL stationary. Frequently, QoL decreases as the severity of CKD rises [35,36], albeit study results can be heterogenous [37]. These discrepancies in reported findings may stem from the tools used, the etiology of CKD, the degree of patient's adherence to their prescriptions of RONS, etc.…”
Section: Discussionmentioning
confidence: 95%